Clinical characteristics and in-hospital mortality in patients with acute kidney injury undergoing hemodialysis at the Hospital Nacional Guillermo Almenara Irigoyen, EsSalud, 2014-2015 - Fernandez-Burga, Antonio (2019)
There are no official data on patients with acute kidney injury (AKI) in Peru. Most of the information comes from isolated centers in other countries. Objective: To describe the clinical characteristics and inhospital mortality in patients with acute kidney injury undergoing hemodialysis at a third level hospital in Peru. Methods: A cross-sectional study. Demographic, clinical, and mortality data were collected from patients diagnosed with AKI undergoing hemodialysis at the Hospital Nacional Guillermo Almenara Irigoyen EsSalud during 2014-2015. Results: 183 patients were included. The average age was 58 years and 57% were male. Ninety percent of patients were admitted through emergency services (EMG). Patients were hospitalized in the intensive care unit (ICU), EMG rooms and other hospitalization areas in 40%, 27% and 33% of cases, respectively. The most frequent causes of AKI were sepsis (58%), heart failure (8%) and obstructive uropathy. In-hospital mortality rate was 55% (n = 100). The deceased patients showed a higher frequency of sepsis (71 vs. 38; p = 0,001) and multiorgan failure (90 vs. 56; p <0,001) compared to alive patients. Conclusions: Patients with AKI had a mean age of 59 years and most were hospitalized in the ICU. The most frequent cause of AKI was sepsis. In-hospital mortality was 55% and was significantly associated with the presence of sepsis and multiorgan failure.